UPAYA MENINGKATAN PEMAHAMAN MATERI NORMA DAN ATURAN DI MASYARAKAT MELALUI MEDIA PANORAMA PADA MATA PELAJARAN PANCASILA SISWA KELAS V B SD NEGERI 060912 MEDAN - Rosalya Marbun; Chairannisa Amelia; Jamilah Farah Dhiba (STKIP Subang, 2024)
With reference to Norms and Rules in Society in particular, the goal of this study is to improve students' understanding of Pancasila education material utilising the panoramic medium of class V B at SD Country 060912 Medan.